Transcutaneous Electrical Spinal Cord Stimulation to Promote Recovery in Chronic Spinal Cord Injury - Tefertiller, Candace; Rozwod, Meghan; VandeGriend, Eric; Bartelt, Patricia; Sevigny, Mitch; Smith, Andrew C. (Frontiers in Rehabilitation Sciences, 2022)
Objective: To evaluate the impact of using transcutaneous electrical spinal cord stimulation (TSCSTSCS) on upper and lower extremity function in individuals with chronic spinal cord injury (SCI). Design: Prospective case series. Setting: SCI specific rehabilitation hospital. Participants: A convenience sample (N = 7) of individuals with tetraplegia who had previously been discharged from outpatient therapy due to a plateau in progress. Interventions: Individuals participated in 60 min of upper extremity (UE) functional task-specific practice (FTP) in combination with TSCS and 60 min of locomotor training in combination with TSCS 5x/week. Main Outcome Measures: The primary outcome for this analysis was the Capabilities of Upper Extremity Test (CUE-T). Secondary outcomes include UE motor score (UEMS), LE motor score (LEMS), sensation (light touch and pin prick), Nine-Hole Peg Test, 10 meter walk test, 6 min walk test, and 5 min stand test. Results: Seven individuals (four motor complete; three motor incomplete) completed 20–80 sessions UE and LE training augmented with TSCS and without any serious adverse events. Improvements were reported on the CUE-T in all seven individuals. Two individuals improved their ASIA impairment scale (AIS) classification (B to C; C to D) and two individuals improved their neurologic level of injury by one level (C4–C5; C5–C6). Sensation improved in five individuals and all four who started out with motor complete SCIs were able to voluntarily activate their LEs on command in the presence of stimulation. Conclusion: Individuals with chronic SCI who had previously demonstrated a plateau in function after an intensive outpatient therapy program were able to improve in a variety of UE and LE outcomes in response to TSCS without any adverse events. This was a small pilot study and future fully powered studies with comparative interventions need to be completed to assess efficacy.